CONSTRAINT-INDUCED MOVEMENT THERAPY FOR LOWER EXTREMITY BALANCE AND FUNCTION IN POST-STROKE PATIENTS: A LITERATURE REVIEW - Muhamad Elfitra Salam; Nurul Aini; Nisa Hanifah; Zakir Burhan (Indonesian Journal of Physiotherapy, 2026)
Background: Constraint-induced movement therapy (CIMT) has demonstrated effective as a neurorehabilitation intervention for addressing "learned non-use" and enhancing functional independence in stroke patients. However, its application to lower extremities (LE-CIMT) remains relatively unexplored. Several studies have shown inconsistent results, particularly regarding the effects of LE-CIMT on balance and lower extremity function in post-stroke patients. Objective: To evaluate the impact of LE-CIMT on balance and lower extremity function in post-stroke patients. Method: A literature review was conducted by searching for relevant articles in PubMed, Physiotherapy Evidence Database (PEDro), Cochrane Library, and Google Scholar from December 2024 to February 2025. Selected articles were appraised using the PEDro scale to assess the level of bias in randomized controlled trials. Results: Seven articles meeting the inclusion and exclusion criteria were identified, all with moderate levels of bias. Data extraction revealed significant improvements (p<0.05) in balance and lower extremity function following LE-CIMT intervention. These improvements are attributed to mechanisms of cortical reorganization. Conclusion: LE-CIMT demonstrates positive effects on balance and lower extremity function in post-stroke patients. Keywords: Balance, CIMT, Lower Extremity, Stroke.